Grasslands of Chakrata Forest Division, District Dehra Dun - Agarwal, S. C. (Indian Forester, 1959)
The Chakrata forest division, locally known as Jaunsar Bawar, consists of mountainous region with elevations varying from 1530' to 10,905'. It can be divided into four zones--(1) Subtropical zone having mostly the plains grasses like Dichanthium annulatum, Bothriochloa pertusa, Chrysopogon montanus, C. gryllus, Cymbopogon martini, C. jwarancusa, Heteropogon contortus, Ergrostis viscosa, Cynodon dactylon, Chloris montana, C. incompleta, Sporobolus pallidus, Eragrostiella nordioides, Digitaria marginata, D. longiflora along with subtropical grasses like Arundinella setosa and Themada anathera, (2) Temperate-chir zone having generally the sub-tropical grasses like Themeda anathera and Arundinella setosa forming a dominant stand and have an association of the above mentioned plains grasses, (3) Subalpine -deodar zone which is really a transition zone for the grass flora. At lower elevations and warmer aspects the subtropical grasses like Themada anathera and Arundinella setosa associated with some of the plains grasses as seen in the chir zone. But in addition some of the alpine grasses like Argostis spp., Festuca spp., Bromus etc., make their appearance. As the elevation increases the preponderance of the alpine grasses increases and after 8000' elevation they form the dominant stand, (4) The Alpine zone has the alpine association of grasses like Festuca rubra, F. bromoides, F. sibirica, Dactylis glomerata, Agropyron semicostatum, Agrostis spp., Arthraxon species, Avena and Bromus species etc. Management plans for the regions have been suggested.